WHAT MAKES GEN Z MORE ENTREPRENEURIAL? EXPLORING THE POWER OF SELF-LEADERSHIP AND ACTIVE LISTENING - Devita Indria Puteri; Putri Amelia; Maria Grace Herlina (Andromeda : Jurnal Manajemen dan Bisnis Syariah, 2026)
Although there is a growing interest in entrepreneurship among Gen Z, many young adults find it difficult to transform entrepreneurial aspirations into entrepreneurial capabilities. This study investigates the relationship between Self Leadership, Active Listening, and Entrepreneurial Orientation (EO) and the mediating role of Active Listening among Gen Z students. Methodology: A quantitative cross-sectional survey was conducted among 403 Gen Z university students from the higher education institutions in Greater Jakarta, Indonesia. The data were collected via an online questionnaire through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings: The study indicates that Active Listening has a significant positive relationship with EO. Self-leadership greatly enhances Active Listening. Moreover, Active Listening plays a significant mediating role in the relationship between self-leadership and EO, implying that communication competence is an important channel through which self-regulatory abilities promote entrepreneurial tendency. Originality: This research contributes to entrepreneurship and self-leadership literature by introducing Active Listening as a mediating mechanism between individual leadership capability and EO among Gen Z. Implications: The findings indicate that educational institutes and entrepreneurship development programs should enhance both self-leadership and active listening competencies to develop entrepreneurial capabilities among younger generations.